Frontiers in soil ecology—Insights from the World Biodiversity Forum 2022. Issue 4 (11th November 2022) - Eisenhauer, Nico; Bender, S. Franz; Calderón‐Sanou, Irene; de Vries, Franciska T.; Lembrechts, Jonas J.; Thuiller, Wilfried; Wall, Diana H.; Zeiss, Romy; Bahram, Mohammad; Beugnon, Rémy; Burton, Victoria J.; Crowther, Thomas W.; et al.
Abstract: Global change is affecting soil biodiversity and functioning across all terrestrial ecosystems. Still, much is unknown about how soil biodiversity and function will change in the future in response to simultaneous alterations in climate and land use, as well as other environmental drivers. It is crucial to understand the direct, indirect and interactive effects of global change drivers on soil communities and ecosystems across environmental contexts, not only today but also in the near future. This is particularly relevant for international efforts to tackle climate change like the Paris Agreement, and considering the failure to achieve the 2020 biodiversity targets, especially the target of halting soil degradation. Here, we outline the main frontiers related to soil ecology that were presented and discussed at the thematic sessions of the World Biodiversity Forum 2022 in Davos, Switzerland. We highlight multiple frontiers of knowledge associated with data integration, causal inference, soil biodiversity and function scenarios, critical soil biodiversity facets, underrepresented drivers, global collaboration, knowledge application and transdisciplinarity, as well as policy and public communication. These identified research priorities are not only of immediate interest to the scientific community but may also be considered in research priority programmes and calls for funding. Abstract :